Study on material structure evolution of steam turbine rotor under thermal cycling fatigue load. (10th May 2021) - Su, Jun; Wang, Xuan; Liu, Lixin
In order to improve the structural strength of the turbine rotor, the dynamic circuit and driving mechanical model of the turbine rotor are established under the thermal cycle fatigue load. The numerical simulation principle of the stress yield evolution process of the rotor structure is analysed. The closed vector method and Lagrange equation are used to establish the mechanical analysis and yield stress model, and the mechanical principle of the thermal cycle fatigue load of the rotor is analysed. On this basis, the yield stress evaluation model is established to realise the material structure evolution analysis. The results show that the method can provide higher accuracy and lower yield stress estimation results, with an average error of 15.74% lower than that of the traditional method, which shows that the method can improve the anti-interference ability of turbine rotor drive and the stress intensity of rotor material structure, with good convergence.